Addressing Challenges in the Energy Sector in Israel - Hemmings, Philip (OECD Publishing, 2011)
Offshore natural-gas discoveries have released Israel from complete reliance on imported primary fuels and are allowing for a cleaner energy mix. Furthermore, additional production will soon come on stream, and there is a reasonable chance of new commercially viable gas finds, and possibly of oil too. The authorities have overhauled the system of royalties and taxes, although how best to use the resulting revenues remains the subject of debate. Concerns about competition in the gas sector have risen following the disruption of imports via the pipeline from Egypt, which has strengthened the market position of the lead consortium developing the offshore fields. Competition concerns in the electricity sector have been longstanding due to sluggish reform away from monopoly provision by the state-owned incumbent. As elsewhere, energy use has important environmental side-effects. A comprehensive plan for reducing greenhouse-gas emissions has been developed recently, which relies primarily on energy-efficiency measures and an increase in the share of renewable-electricity product. This Working Paper relates to the OECD 2011 Economic Survey of Israel (www.oecd.org/eco/surveys/Israel)
Keywords: Economics; Israel